Assessing the impact of armed conflict on the progress of achieving 17 sustainable development goals - Di Wang; Mengmeng Hao; Ning Li; Dong Jiang (iScience)
Summary: With global armed conflicts reaching a 30-year high in 2023, understanding their impact on the progress of Sustainable Development Goals (SDGs) is crucial. Here, we used the propensity score matching method to assess the specific impacts of armed conflict on achieving the 17 SDGs in affected countries from 2000 to 2021. The results indicate that, compared to the hypothetical scenarios without conflict, progress on more than half of the SDGs has slowed by over 5% in countries experiencing armed conflict. This slowdown is most acute in SDG 9 (Industry, Innovation, and Infrastructure) and SDG 4 (Quality Education), where impediments exceed 10%. Without such conflicts, these countries could have seen advancements in over one-third of the SDGs, moving from low to moderate levels, or from moderate to high levels of achievement. This information provides insights for conflict-affected countries to identify key SDGs and navigate out of developmental challenges.